A Novel Rapid IL-6 Release Assay Using Blood Mononuclear Cells in the Differential Diagnostics of Patients after Skin Localized Hypersensitivity Reactions to Drugs - Mathias, Baló-Banga Joseph (Perspective of Recent Advances in Medical Research Vol. 10, 2023)
Interleukin-6 (IL-6) has a central role in the orchestration of immune response. It is proven to have a key role in the transition from innate to adaptive immune reaction. It has both pro and anti-inflammatory properties. Normal values in serum are below 7 pg/ml. Its effects are largely dependent on the presence of its receptor (IL-6R) which is bound either on the cell surface or exists in free soluble form (sIL-6R). The binding of a small molecular weight molecule (i.e a drug) to its receptor and to HLA molecules on T-memory cells does not involve necessarily hapten presentation but can proceed very rapidly by pharmacologic interaction (p-i) activating immune mechanisms (Pichler). This in turn can activate pro-inflammatory mechanisms and start through the IL-6 release a response sequence both in vitro and in vivo. Our aim was to measure secreted IL-6 from the mononuclear cells’ supernatants after 20 minutes incubation in a large cohort of patients after both of early and late skin hypersensitivity (HS) reactions to various common drugs (43) arising from the history and compare the results with those of an appropriate control group and validate them by in vivo tests. Together 213 patients with the history of adverse effects to drugs and 48 control subjects were involved. The majority of patients (159) and all the controls’ mononuclear cells were separated and after incubation with a standard series of 0.15-0.5 µmol solutions of various drugs for 20’ together with negative and positive controls, IL-6 released into the cell free supernatants was measured by ELISA assay. The tests were correlated to the earlier diagnostic method elaborated to measure nuclear rearrangements after similarly short incubation with drugs named chromatin activation test. The exact conditions necessary for reproducible and clinically relevant results were established by comparing two groups of similar clinical phenotype composition. The method offering high sensitivity was selected out. Sensitivity of 85.4% and specificity of 82.4% of the IL-6 release assay was found against the in vivo tests. In the molecular mass range of 76-4000 Da, IL-6 release was dependent on the clinical phenotype but not on the evoking drug(s). Reactivity of mononuclear cells at the lowest or at multiple drug test concentrations reflected clinical severity per diagnoses, or in HS cases with varying skin involvement the area, involved. The largest pharmacological subgroup causing positive test results was of nonsteroidal anti-inflammatory drugs (NSAID). Consisting of 51 patients and 9 controls, respectively was tested by 9 different non-steroidal anti-inflammatory drugs and compared with another group of patients (56 with immediate or early HS reaction in their history) using determination of specific IgE against NSAID from their sera within one year after the event. In vivo tests (patch, intradermal and oral provocations) were performed in parallel to in vitro testing. The positivity ratio of validated test results was nearly double within the IL-6 release-tested group after adverse reactions due to NSAID compounds as compared to specific IgE tested patients’ positivity in their sera (65.4% vs. 36.5%). The mechanism of IL-6 transsignaling which is behind the life threatening “Cytokine Release Syndrome” is believed to account for this novel diagnostic test.